2014
DOI: 10.7861/clinmedicine.14-6-663
|View full text |Cite
|
Sign up to set email alerts
|

When to suspect ‘funny’ diabetes

Abstract: Diabetes comes in many shapes and forms. It is important for the general physician to recognise when clinical characteristics, response to treatment and associated features suggest an alternative variety of diabetes, over and above the traditional type 1 and type 2 forms which are far more common. Key to these suspicions are taking a clear history of the development of the diabetes and being aware of the family history.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Features of monogenic diabetes and of monogenic diabetes type 5 [5][6][7][8][9] Some distinguishing features of monogenic diabetes [5][6][7] • Young age at diagnosis (typically <25 years, although patients can be older) guishing features of monogenic diabetes in general and monogenic diabetes type 5 in particular. [5][6][7][8][9] In monogenic diabetes type 5, reduced insulin secretion is due to beta-cell dysfunction, which is related to pancreatic atrophy. 10 The commonest renal abnormality is cystic disease (66% of cases) although the most specific phenotype is familial hypoplastic glomerulocystic kidney disease.…”
Section: Discussionmentioning
confidence: 99%
“…Features of monogenic diabetes and of monogenic diabetes type 5 [5][6][7][8][9] Some distinguishing features of monogenic diabetes [5][6][7] • Young age at diagnosis (typically <25 years, although patients can be older) guishing features of monogenic diabetes in general and monogenic diabetes type 5 in particular. [5][6][7][8][9] In monogenic diabetes type 5, reduced insulin secretion is due to beta-cell dysfunction, which is related to pancreatic atrophy. 10 The commonest renal abnormality is cystic disease (66% of cases) although the most specific phenotype is familial hypoplastic glomerulocystic kidney disease.…”
Section: Discussionmentioning
confidence: 99%
“…Umpierrez and colleagues demonstrated that the acute glucose toxic presentation of KPD blunts beta cell functioning, but is reversible. 16 Reversible (yet still reduced) beta cell dysfunction suggests that exogenous insulin administration may not be necessary for an extended period of time. 15 Diagnostic clues to KPD include the symptoms of glucose toxicity discussed above, coupled with ketosis and/or DKA, negative diabetes-related autoantibodies, and a normal C-peptide.…”
Section: ■ Diagnosis and Diagnostic Cluesmentioning
confidence: 99%
“…As with all forms of diabetes, in a variety of settings, it is important to be increasingly aware of the many different types of monogenic diabetes and their associated complications …”
mentioning
confidence: 99%